Sequential energy and electron transfer in polynuclear complex sensitized TiO2 nanoparticles - Verma, Sandeep; Kar, Prasenjit; Banerjee, Tanmay; Das, Amitava; Ghosh, Hirendra N. (Journal of Physical Chemistry Letters, 2012)
Polynuclear–polypyridyl complexes exhibit a directional energy-transfer property that can improve their photosensitization activity. In the present work, the energy-transfer process is explored in a trinuclear Ru2∧Os1 complex using transient absorption spectroscopy. This study reveals an efficient excitation energy transfer from the terminal (RuII complex) to the core (OsII complex) region in the ultrafast time domain (400 fs–40 ps). The excitation energy funnel is useful in improving the functionalized core activity. This is evidenced in an interfacial electron-transfer study of Ru2∧Os1, Ru2∧Ru1, and Os1 complex sensitized TiO2 nanoparticle (TiO2 NP) systems. The intramolecular energy transfer causes sequential excitation of the core part of the Ru2∧Os1 complex, which leads to multiexponential electron injection into TiO2 NP. Besides this, the electronic coupling between the metal ion centers stabilizes the positive charge within the trinuclear complex, which results in a slow charge recombination reaction. This study shows that polynuclear complexes can be very useful for their panchromatic effects, unidirectional energy- and electron-transfer properties.

Synthesis, steady-state, and femtosecond transient absorption studies of resorcinol bound ruthenium(ii)- and osmium(ii)-polypyridyl complexes on nano-TiO2 surface in water - Banerjee, Tanmay; Kaniyankandy, Sreejith; Das, Amitava; Ghosh, Hirendra Nath (Inorganic Chemistry, 2013)
The synthesis of two new ruthenium(II)- and osmium(II)-polypyridyl complexes 3 and 4, respectively, with resorcinol as the enediol anchoring moiety, is described. Steady-state photochemical and electrochemical studies of the two sensitizer dyes confirm strong binding of the dyes to TiO2 in water. Femtosecond transient absorption studies have been carried out on the dye–TiO2 systems in water to reveal <120 fs and 1.5 ps electron injection times along with 30% slower back electron transfer time for the ruthenium complex 3. However, the corresponding osmium complex 4 shows strikingly different behavior for which only a <120 fs ultrafast injection is observed. Most remarkably, the back electron transfer is faster as compared to the corresponding catechol analogue of the dye. The origin and the consequences of such profound effects on the ultrafast interfacial dynamics are discussed. This Article on the electron transfer dynamics of the aforesaid systems reinforces the possibility of resorcinol being explored and developed as an extremely efficient binding moiety for use in dye-sensitized solar cells.

Superior grafting and state-of-the-art interfacial electron transfer rates for newly designed geminal dicarboxylate bound ruthenium(II)- and osmium(II)-polypyridyl dyes on TiO2 nanosurface - Banerjee, Tanmay; Biswas, Abul Kalam; Reddy, Upendar G.; Sahu, Tuhin Subhra; Das, Amitava; Ganguly, Bishwajit; Ghosh, Hirendra Nath (Journal of Physical Chemistry C, 2014)
Two new Ru(II)-/Os(II)-polypyridyl based sensitizer dyes with geminal dicarboxylic acid group as the binding unit for superior grafting of the dye to TiO2 have been designed and synthesized. Steady-state photochemical studies of the two sensitizer dyes in presence of TiO2 in water confirm strong binding of the dyes to TiO2. Femtosecond transient absorption studies of these newly synthesized dyes on TiO2 nanosurface have been carried out in water and the results have been compared with those for the corresponding 4,4'-dicarboxy-2,2'-bipyridine analogues of the dyes. While the charge recombination rates are considerably slower, interestingly, the electron injection rates are very fast for multiple saturated C-C linkages present between the chromophoric core and the anchoring moiety. The origin and the consequences of such profound effects on the ultrafast interfacial dynamics are discussed. This is the first report on the ultrafast transient absorption studies of dyes with geminal dicarboxylic acid binding groups, which we believe will add significantly to the present research efforts toward the development of robust and efficient dyes for use in dye solar applications.